Taking a walk : a book in two languages = Caminando : un libro en dos lenguas - Emberley, Rebecca (New York : Scholastic, 1990)
Labeled illustrations and Spanish and English text introduce the things a child sees while on a walk.
English and Spanish.
BR
Keywords: Picture dictionaries, Spanish; Picture dictionaries, English; Spanish language -- Glossaries, vocabularies, etc; English language -- Glossaries, vocabularies, etc; Spanish language materials -- Bilingual; Picture dictionaries